Evaluation of response to selection: effect of freezing on weaning weight and post-weaning daily gain in rabbits - Cifre J.; Baselga M.; Gómez E.A. (Rabbit production in hot climates, 1994)
The effect of freezing, thawing and transfering embryos on weaning weight, daily gain and slaughter weight is studied in rabbits. A significant and depressing effect has been detected on daily gain. The implications of this effect on the use of frozen embryos to evaluate genetic response to selection for daily gain are discussed.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)